Thermodynamic assessment of chemical and electrochemical stability of vanadium silicides - P.A. Nikolaychuk (Учёные записки Казанского университета: Серия Естественные науки)
The phase and chemical equilibria in the V–Si system at 25 °C were considered. The possible maximum solid solubility of Si in bcc-V at 25 °C was estimated. The thermodynamic activities of the components in this saturated solution were calculated. The state diagram of the V–Si–O system at 25 °C was plotted and the characteristics of their invariant conditions were calculated. The activity – pH diagram for vanadium(V) compounds was plotted. The potential – pH diagram of the V–Si–H2O system at 25 °C, air pressure of 1 bar, and activities of ions in solution equal to 1 mol/L was plotted. The thermodynamic analysis of chemical and electrochemical stability of the V–Si system alloys was performed.